Experiments in self-determination : histories of the outstation movement in Australia - Peterson, Nicolas; Myers, Fred R., 1948- (Monographs in anthropology series., 2016)
The authors focus is on the outstation movement of the 1970's, that drive by remote area Aboriginal groups in the centre and the north to escape from regimented and overcrowded community settlements, and consolidate a new life-path in the bush. Most of the outstations lie in the Northern Territory.